2012
DOI: 10.1111/jace.12046
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodispersed Spherical Yttrium Aluminum Garnet (YAG) Powders by a Homogeneous Precipitation Method

Abstract: Monodispersed yttrium aluminum garnet (YAG) powders have been synthesized via homogeneous precipitation method from the mixed solutions of yttrium nitrate, aluminum nitrate, and ammonium aluminum sulfate using urea as the precipitant. The molar ratio of aluminum nitrate to ammonium aluminum sulfate has a significant effect on morphology and particle size of the precursor powders. It was found that spherical precursor particles can be obtained when the ratio is 1:1. During the homogeneous precipitation process,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…YAG:Ce phosphor microspheres are thus alternatively made via crystallizing the glassy microbeads quenched from melt droplets produced with laser heating [51]. Xu et al [52] identified that, with nitrate as the rare-earth source in UBHP, the aluminum source plays an essential role in the formation of precursor microspheres for YAG:Nd. They found that ammonium aluminum sulfate (alum) is indispensable and the optimal alum/Al(NO 3 ) 3 molar ratio is 1/1.…”
Section: Down-conversion (Dc) Phosphors Based On Gagmentioning
confidence: 99%
“…YAG:Ce phosphor microspheres are thus alternatively made via crystallizing the glassy microbeads quenched from melt droplets produced with laser heating [51]. Xu et al [52] identified that, with nitrate as the rare-earth source in UBHP, the aluminum source plays an essential role in the formation of precursor microspheres for YAG:Nd. They found that ammonium aluminum sulfate (alum) is indispensable and the optimal alum/Al(NO 3 ) 3 molar ratio is 1/1.…”
Section: Down-conversion (Dc) Phosphors Based On Gagmentioning
confidence: 99%
“…developed this method and made it finally suitable for the preparation of fully transparent ceramics and advanced luminescent materials. Among which, work accomplished by Sun [43] etc. in 2012 should be emphasized.…”
Section: Preparation Of Binary Particlesmentioning
confidence: 99%
“…FE-SEM micrographs of (a) YAG precursor during the precipitation process and (b) powders calcined at 1000 1C[43].…”
mentioning
confidence: 99%
“…To obtain Yb:YAG transparent ceramics with desired microstructure, its fabrication technology is very important. In recent years, many efforts have been made on YAG-based ceramics related to the synthesis of high-purity and agglomeration-free powders [8][9][10], amount and choice of sintering additives [11][12][13], optimization of sintering process [14][15][16], post-treatment [17][18][19][20], etc. Powder shaping technology was also important for obtaining highly transparent ceramics.…”
Section: Introductionmentioning
confidence: 99%